The importance of commitment to information in electronic contracting - Mohammed Fawaz Sabah (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The information obligation is intended to inform the consumer of all information related to the goods or service provided by the producer. This information includes all the data available to him regarding the conservation or maintenance of the product or the proper method of its use or the risk profile therein and the precautions to be taken to prevent the risks. Greater commitment to information in electronic contracting, which is a distance, and for this reason: newly emerged new protection for electronic consumers and highlights the commitment to the media in the forefront of this protection, where the necessity of the consumer is indispensable, the duty of the professional imposed by law and Arranged on a breach of responsibility.